Influence of medium modifications (optimization) on high nematicidal activity of the fermentation broth of Clostridium beijerinckii - Liu, Shuang; Zhang, Kejun; Yu, Yun; Lian, Xinglong; Jiang, Lanyuwen; Meng, Fanqi; Wang, Yuanyuan; Zhu, Xiaofeng; Duan, Yuxi (Frontiers in Bioengineering and Biotechnology, 2024)
The nematode species Meloidogyne incognita has been responsible for significant financial losses within the agricultural sector. Nematophagous bacteria, characterised by their extensive distribution and broad spectrum of hosts, exhibit remarkable efficacy as natural antagonists against nematodes. Sneb518 (Clostridium beijerinckii) fermentation broth displayed substantial biocontrol activity against M. incognita in previous research. Optimizing fermentation conditions is a fundamental technique for dramatically enhancing end product performance. There has been no such study conducted yet on enhancing the nematicidal activities of Sneb518 (Clostridium beijerinckii) fermentation using response surface methodology (RSM). Thus, the influence of strain Sneb518 fermentation media and conditions on nematicidal activity was examined using the three-factor technique and a Plackett-Burman design, and the interaction between various fermentation factors was examined using a Box-Behnken design. The present study employed response surface methodology (RSM) to examine and enhance the nematicidal activity of Sneb518 culture filtrates by identifying and optimising the influential components. Glucose, peanut cake flour, and potassium chloride as carbon, nitrogen, and inorganic salts displayed considerably increased nematicidal potential in the present study. Furthermore, the corrected mortality of J2 ranged from 52.24% to 91.15% when utilizing the Box-Behnken design. These findings clearly support the application of RSM for medium optimization. Moreover, the outcomes of the validation experiment corresponded to the model predictions. This research has enhanced the biocontrol ability of C. beijerinckii to control M. incognita and this research has led to the advancement of new biocontrol agents.